Geodetic surveying studies for civil engineering students at Tallinn University of Technology - Ustinova, Nelli; Kala, Vello; Mill, Tarvo; Ellmann, Artu (Geodesy and Cartography, 2012)
Studies in the Tallinn University of Technology are based on a modular system, where geodetic surveying comprises a self-contained study module in the curricula of all civil engineering specialities. Due to geodetic surveying being taught to all first year students of civil engineering, it serves as a touchstone to test a student’s suitability for an engineering specialism. Future civil engineers are taught basic geodetic measurements and how to use optical theodolite, levelling instrument and laser level. The paper gives an overview of geodetic surveying lectures, laboratory classes and field survey camp. Teaching and assessment are based on learning outcomes. Students who have passed the exam are allowed to participate in the summer field survey camp, the aim of which is consolidating the knowledge acquired throughout the year and practising teamwork.